Catalogue of the Australian social wasps (Hymenoptera: Vespidae) - Carpenter, James M.; Brown, Graham R. (Zootaxa, 2022)
A catalogue of the social wasps occurring in Australia is presented. New synonymies include Vespa cohabitatrix Curtiss, 1938 (= Polistes olivaceus (DeGeer, 1773)) and Vespula vulgaris vetus Eck, 1999 (= Vespula vulgaris (Linnaeus, 1758)).